PROFESSORS' VIEW ON THE LEARNING POSSIBILITIES OF NURSING AND MEDICINE STUDENTS FROM THE EXPERIENCE IN PROFESSIONAL PRACTICE AND ENCOUNTERED CHALLENGES - Ghezzi, Joyce Fernanda Soares Albino; Higa, Elza de Fátima Ribeiro; Lemes, Monike Alves; Peres, Cassia Regina Fernandes Biffe; Marin, Maria José Sanches (Cadernos de Educação Tecnologia e Sociedade, 2019)
The challenge of training health professionals in Brazil points to the political commitment both to education and to society, as it requires, in addition to technical skills, improvement in the intra and interpersonal process as pointed out in the National Curricular Guidelines. The purpose of this article is to understand the Professors’ perception about the students’ learning of the Nursing and Medical courses included in the Family Health Strategy, and to identify the factors related to the teaching work process in the active learning methodology. This Research based on the presuppositions of Hermeneutics-Dialectics. Ten professors from the Nursing and Medicine courses that followed up students in the professional practice scenario participated of the research. The data were obtained through recorded interviews. From the analyses emerged three nuclei of meaning: Significant and relevant learning; Insecurity for the development of the active methodology and Difficulties in the teaching work. The teachers pointed out the importance of the real scenario for learning and the uncertainties and difficulties of the process. In this sense, these results can subsidize required changes in the educational process.